A Novel Principles+ Framework for Improving User Experience of Augmented Reality - Tenia Wahyuningrum; Aditya Tama Isdiarto; Robert Hendra Yudianto; Rajermani Thinakaran (Politeknik Negeri Cilacap, 2025)
This study introduces a framework that aligns analysis and synthesis approaches, PRInCiPleS+, to enhance the user experience (UX) for Mooi Indie paintings through Augmented Reality (AR). By integrating cultural depth, emotional engagement, and technical usability, this study aims to revive this traditional art form and engage younger audiences. The customized PRInCiPleS+ design method combines empathy mapping and sustainability considerations to develop an AR application for Instagram filters. This study highlights the role of AR in preserving traditional arts while aligning it with the Sustainable Development Goals. The results of the Mooi Indie AR test using the independent sample T Test method showed no significant difference between users who had never used AR and those who had used AR in terms of user experience. In other words, users who are using AR for the first time and those who have used AR before feel almost the same user experience. The user experience score measured using the UMUX-Lite questionnaire showed that the group of users who had never used AR had a user experience score of 78.15, while the group who had ever used AR was 71.10, which means good. Analytically, Mooi Indie AR still needs some improvement, especially in terms of filter loading time, time required to explore filters, the number of users who use filters, and then save and share them with other users to increase engagement.